Upscaling Kemampuan Siswa/i untuk Menjadi Wirausahawan Sukses di Era Digital - Agung Utama; Tony Wijaya; Winarno Winarno; Rullyana Puspitaningrum Mamengko (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The facts show that currently the ratio of acceptance of vocational graduates in the industry is still quite low. This is due to the large gap between the skills taught in university and the needs of the industry. For this reason, the Directorate General of Higher Education is promoting the Vocational High School Revitalization program. Yogyakarta State University which has the obligation to organize Community Service as one of the Tri Dharma College welcomes the program and cooperates with SMK Negeri 4 Yogyakarta. The focus of this service is to improve the skills of students at SMK Negeri 4 Yogyakarta to become entrepreneurs in the digitalization era. For this reason, the author provides training on Positive Mental in Entrepreneurship, Basic Business Marketing, Basic Business Finance, and Content Marketing. The stages of this service activity are carried out through four stages, namely the collaboration stage, the preparation stage, the training implementation stage, and the activity evaluation stage. Evaluation is carried out in two ways, namely (1) evaluation of activities, this is when training activities are carried out; and (2) final evaluation, this is at the end of program implementation.